2013
DOI: 10.1007/s40279-013-0116-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Location of Bone Bruises Associated with Anterior Cruciate Ligament Injury and Implications for Mechanism of Injury: A Systematic Review

Abstract: Background Bone bruising is commonly observed on magnetic resonance imaging (MRI) after non-contact anterior cruciate ligament (ACL) injury. Objectives The primary objective of this study was to determine if the location and prevalence of tibial and femoral bone bruises after ACL injury can be explained by specific injury mechanism(s). The secondary objective was to determine whether the bone bruise literature supports sex-specific injury mechanism(s). We hypothesized that most studies would report bone brui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
132
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(140 citation statements)
references
References 46 publications
8
132
0
Order By: Relevance
“…Some studies have suggested that the high incidence of bruising near the terminal sulcus and the posterolateral tibial plateau may be due to a pivot shift event in which anterior subluxation occurs concurrently with an ACL tear 17, 23, 53 . Due to the high incidence of bone bruising in the lateral compartment in individuals with ACL injury 53, 57, 62 , some studies have emphasized the importance of valgus rotation 48, 50 . Medial compartment bruising in non-contact injuries has been attributed to anterior tibial translation and internal tibial rotation rather than valgus stress due to the location of femoral condyle bruising relative to tibial plateau bruising 57, 60 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have suggested that the high incidence of bruising near the terminal sulcus and the posterolateral tibial plateau may be due to a pivot shift event in which anterior subluxation occurs concurrently with an ACL tear 17, 23, 53 . Due to the high incidence of bone bruising in the lateral compartment in individuals with ACL injury 53, 57, 62 , some studies have emphasized the importance of valgus rotation 48, 50 . Medial compartment bruising in non-contact injuries has been attributed to anterior tibial translation and internal tibial rotation rather than valgus stress due to the location of femoral condyle bruising relative to tibial plateau bruising 57, 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have reported on the location, volume, intensity, depth, and frequency at which bone bruising occurs with ACL injury 36, 43, 48, 53, 57 , little data is available quantifying the position and orientation of the knee at the time of injury. Thus, in order to assess the repeatability of our measurements, three independent trials of bone bruise outlining were performed on a single knee using the same procedure as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] The location and size of a traumatic BML may be influenced by the mechanism of injury (ie, loading during injury) or the presence of concurrent injuries (eg, compression fracture, meniscal lesion, collateral ligament sprain). 4,[10][11][12][13][14][15] Therefore, the size and location of a traumatic BML within the first few weeks of an ACL injury may provide useful information about the initial injury. Furthermore, the size of a traumatic BML may relate to knee pain or symptoms either because it is a proxy for the severity of the initial injury or because the lesion causes knee pain.…”
mentioning
confidence: 99%
“…3 Several studies have confirmed the higher incidence and greater degree of impaction in the lateral compartment commonly attributed to a pivot shift valgus-loading injury mechanism. 6 The most common pattern observed at MR imaging is a noncontiguous bone contusions on the midportion of lateral femoral condyle and the posterior margin of the lateral aspect of the tibial plateau. Although the presence of bone contusions in the medial compartment of the knee has been previously recognized, its mechanism and clinical relevance remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%